2017
DOI: 10.1063/1.4979649
|View full text |Cite
|
Sign up to set email alerts
|

An oxidation-last annealing for enhancing the reliability of indium-gallium-zinc oxide thin-film transistors

Abstract: The dependence of device reliability against a variety of stress conditions on the annealing atmosphere was studied using a single metal-oxide thin-film transistor with thermally induced source/drain regions. A cyclical switch between an oxidizing and a non-oxidizing atmosphere induced a regular change in the stress-induced shift of the turn-on voltage, with the magnitude of the shift being consistently smaller after annealing in an oxidizing atmosphere. The observed behavior is discussed in terms of the depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The reliability of an EMMO TFT against bias and thermal stress is also known to depend on the presence and the amount of defects in the channel region [11]. Positive gate-bias temperature stress (PBTS) was carried out at 85 °C with Vg set at Von + 20 V. When the non-fluorinated EMMO TFTs were subjected to PBTS, the families of transfer curves shifted in the negative Vg direction (Fig.…”
Section: P-15 / Z Xiamentioning
confidence: 99%
“…The reliability of an EMMO TFT against bias and thermal stress is also known to depend on the presence and the amount of defects in the channel region [11]. Positive gate-bias temperature stress (PBTS) was carried out at 85 °C with Vg set at Von + 20 V. When the non-fluorinated EMMO TFTs were subjected to PBTS, the families of transfer curves shifted in the negative Vg direction (Fig.…”
Section: P-15 / Z Xiamentioning
confidence: 99%
“…A previous study has reported that changing the atmosphere during the annealing treatment process affects the thin film . According to Li et al, the oxygen vacancy ( V O ) in the thin film can be suppressed by the O 2 annealing process, which can improve stability. This is because the O 2 inside the furnace diffuses into the channel layer and fills the V O .…”
Section: Resultsmentioning
confidence: 99%
“…Longer thermal annealing is apparently more effective for driving out hydrogen. The population could be increased by subjecting the TFT to an additional nitrogen (N 2 ) anneal at 350 °C for 10 minutes [13]. The resulting transfer curves are shown in Fig.…”
Section: W=100mmentioning
confidence: 99%